Separable reversible data hiding by vacating room after encryption using encrypted pixel difference - Veeramuthu Venkatesh; R. Anushiadevi; Padmapriya Velupillai Meikandan; Hemalatha Mahalingam; Rengarajan Amirtharajan (Scientific Reports)
Abstract As the number of people using the Internet has increased, more information is stored and accessible daily. As a result, the requirement for information security also grows. In the early stages of data security, cryptography is used. Cryptography turns readable information into an unreadable form. Steganography is the next generation of information security. The main downside of this steganography is that the digital media becomes damaged due to hiding information in digital media. The next stage of information security is Reversible Data Hiding (RDH). This method can restore personal information and digital media without error. The next method, Separable Reversible Data Hiding in Encrypted Digital Media, recovers the digital media and extracts concealed information independently without disturbing or knowing each other. This paper presents a novel Separable Reversible Data Hiding by Vacating Room After Encryption using the Encrypted Pixel Difference (SRDH-VRAE-EPD) method, which combines homomorphic encryption and encrypted pixel differences. The proposed method offers the following advantages. It achieves an embedding rate of 1.2 bpp, significantly improving upon standard VRAE algorithms while allowing for lossless data extraction and image recovery. The encrypted image ensures high security against various attacks, including statistical, differential, and chosen plaintext attacks, and it allows for the extraction of secret data and recovery of the original image independently, making it a separable process.